2022
DOI: 10.1037/xlm0001072
|View full text |Cite
|
Sign up to set email alerts
|

Memory resources recover gradually over time: The effects of word frequency, presentation rate, and list composition on binding errors and mnemonic precision in source memory.

Abstract: Normative word frequency has played a key role in the study of human memory, but there is little agreement as to the mechanism responsible for its effects. To determine whether word frequency affects binding probability or memory precision, we used a continuous reproduction task to examine working memory for spatial positions of words. In three experiments, after studying a list of five words, participants had to report the spatial location of one of them on a circle. Across experiments we varied word frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 58 publications
(151 reference statements)
2
15
0
Order By: Relevance
“…A precise characterization of source memory retrieval requires an account of the effect of temporal contiguity (and other forms of contiguity explored in the following subsections) on source retrieval. Recently in the source memory literature, Popov et al (2021) investigated errors in a similar paradigm to ours and found that misbinding errors were most likely to come from neighboring serial positions, demonstrating a relationship between the probability of binding errors and serial position that can be explained as an effect of temporal contiguity. Building upon this finding, in our modeling, instead of freely estimating the probability of intrusions from each lag as Popov et al ( 2021) did, we assume that intrusion probability, like perceived similarity, decreases exponentially with increasing temporal distance (Howard & Kahana, 2002a;Murdock, 1997;Logan, 2021;Osth et al, 2018).…”
Section: Sources Of Intrusionssupporting
confidence: 55%
See 3 more Smart Citations
“…A precise characterization of source memory retrieval requires an account of the effect of temporal contiguity (and other forms of contiguity explored in the following subsections) on source retrieval. Recently in the source memory literature, Popov et al (2021) investigated errors in a similar paradigm to ours and found that misbinding errors were most likely to come from neighboring serial positions, demonstrating a relationship between the probability of binding errors and serial position that can be explained as an effect of temporal contiguity. Building upon this finding, in our modeling, instead of freely estimating the probability of intrusions from each lag as Popov et al ( 2021) did, we assume that intrusion probability, like perceived similarity, decreases exponentially with increasing temporal distance (Howard & Kahana, 2002a;Murdock, 1997;Logan, 2021;Osth et al, 2018).…”
Section: Sources Of Intrusionssupporting
confidence: 55%
“…Specifically, we found that the temporal and spatial proximity of nontargets to targets at study affected the probability of intrusions. The temporal component of our model builds upon the Popov et al (2021) finding that intrusions are more likely to come from adjacent lags than distant lags. Rather than separately estimate intrusions from different lags, we constrained our temporal gradient model by assuming that intrusions follow an exponential decay function with directional asymmetry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current work, we apply the SAC model of episodic memory to infer the amount of available resources during encoding, based on behavioral data during recall. The resource assumption in the SAC model has been supported by numerous behavioral findings (Kowialiewski et al, 2021;Mizrak & Oberauer, 2021;Popov et al, 2019;Popov & Reder, 2020;Popov et al, 2021). The inferred resource availability will then be used to validate the neural index of resource availability, obtained from the neural signal during encoding.…”
Section: Sac Model Of Resource Availabilitymentioning
confidence: 91%